The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1988
DOI: 10.1121/1.397064
|View full text |Cite
|
Sign up to set email alerts
|

Reexamination of dynamic problems of elasticity for negative Poisson’s ratio

Abstract: Recently, isotropic elastic materials with a negative Poisson’s ratio have been manufactured. Since most of the theoretical results of linear elasticity focus on a positive Poisson’s ratio, the need arises for their extension and reexamination. The above materials may have a variety of technological applications so the motivation for this study is not purely academic. The article deals first with some of the limit cases arising when Poisson’s ratio takes on an extreme value. For models represented by these lim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
51
0

Year Published

1993
1993
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(51 citation statements)
references
References 0 publications
0
51
0
Order By: Relevance
“…[32] The resilience of a cushion material is related to the comfort experienced by the user, and the double curvature property may be useful in ensuring mattresses, for example, provide support where it is needed for the ªdoubly curvedº human body. [33] Dynamic effects have been investigated and interesting effects on properties such as the reflection of elastic waves at surfaces have been predicted [34] for auxetic materials. Subsequent studies, [35±38] partially funded by the US Office of Naval Research, have demonstrated enhanced sound and vibration absorption for auxetic foams.…”
Section: Foamsmentioning
confidence: 99%
“…[32] The resilience of a cushion material is related to the comfort experienced by the user, and the double curvature property may be useful in ensuring mattresses, for example, provide support where it is needed for the ªdoubly curvedº human body. [33] Dynamic effects have been investigated and interesting effects on properties such as the reflection of elastic waves at surfaces have been predicted [34] for auxetic materials. Subsequent studies, [35±38] partially funded by the US Office of Naval Research, have demonstrated enhanced sound and vibration absorption for auxetic foams.…”
Section: Foamsmentioning
confidence: 99%
“…The dynamic behaviour of auxetic materials has been investigated by several authors [7][8][9][10][11][12]. The possible use of auxetic materials for viscoelastic damping applications has been examined in [10,13], where biphasic auxetic composite showed loss tangent exceeding lower Voigt limit and close to Hashin upper bound.…”
Section: Introductionmentioning
confidence: 99%
“…The mechanical properties of these alternatives to solid components have thoroughly been investigated by (Zang and Ashby, 1991;Gibson et al, 1997;Evans et al, 2001;Wicks and Hutchinson, 2001) among others. In dynamics, specific attention has been placed on surface and Rayleigh wave propagation behavior in isotropic homogeneous linear elastic solids with negative Poisson's ratios (Lipsett and Beltzer, 1988). Among the proposed innovative geometries, chiral topologies (Lakes, 1991;Prall and Lakes, 1996) feature a unique geometric configuration which can be exploited for the design of innovative structural components.…”
Section: Introduction Imentioning
confidence: 99%